Guidance and Counseling Strategies for Addressing Slow Learner Students at SMPN 17 Surabaya - Hasanah, Laila Uswatun; Cholil, Cholil (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study aims to describe the guidance and counseling (GC) strategies used to address slow learner students at SMPN 17 Surabaya. The research employs a qualitative approach with a case study design, involving the guidance counselor as the primary informant. Data were collected through in-depth interviews, observations of the learning process, and documentation of counseling services. Data analysis was conducted thematically through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the identification of slow learner students is carried out through the inclusion pathway and mid-semester psychological testing, followed by needs assessment, parent consultation, and coordination with subject teachers. The GC strategies implemented include individual counseling, structured learning guidance, group guidance, curriculum adjustments through material simplification, and collaboration with homeroom teachers, subject teachers, psychologists, and accompanying student assistants. These strategies have proven effective in improving attention, motivation, and self-adjustment abilities among some slow learner students. This study underscores the importance of guidance and counseling services that are collaborative, continuous, and differentiated according to student characteristics. The findings are recommended as a basis for strengthening the SOP for identifying slow learners and enhancing the competence of guidance counselors in providing differentiated services.